Optimization of drying temperature and vacuum pressure on the decoloration and composition crude ﬁsh oil - Esquivel-Paredes, Lourdes (2018)
The objective of this study was to determine the optimal parameters of decolorization of crude oil to obtain a semi-refined fish oil of acceptable quality; response surface methodology was used, considering a central composite design with two factors: Vacuum pressure (0.13-0.7 bar) and drying temperature (96-124°C); having as dependent variables the percentage of free fatty acids (% AGL) and color of the oil. The raw material and the optimum finished product were characterized physico-chemically, which was obtained under the operating conditions: drying temperature of 110 ° C and 0.13 bar vacuum. The finished product indicated a percentage of free fatty acids of 0.27 ± 0.01% and CieLab colour with coordinates L: 48.69 ± 0.88, a: -4.28 ± 0.26 and b: 35.03 ± 0.85, which Is equivalent to color 6 -7 in Gardner scale, compliance with the industrial specifications.